Effect of Ocular Magnification on Macular Choroidal Thickness Measurements Made Using Optical Coherence Tomography in Children. (2nd November 2022) - Deng, Junjie; Jin, Jiali; Zhang, Bo; Zhang, Siqi; Wang, Jingjing; Xiong, Shuyu; Cheng, Tianyu; Liu, Kun; Huang, Jiannan; He, Xiangui; Xu, Xun
Abstract: Purpose: To evaluate the relationship between ocular magnification correction and macular choroidal thickness (ChT) measurements in children, and to demonstrate when ocular magnification correction is necessary. Methods: Chinese children aged 6–9 years with various refractive statuses were included. Swept-source optical coherence tomography was used to measure macular ChT. A self-designed program was adopted to simulate ChT changes in each sector of the ETDRS grid in the macula under various simulated axial lengths (ALs). Results: ChT measurements were not affected for all simulated ALs in over 95% of the individuals in the central fovea. In the inferior, superior, and temporal parafoveal sectors, the extent of AL that may include 95% of the individuals narrowed from approximately 22.0 mm to 27.2 mm. In the nasal parafoveal sector and inferior, superior, and temporal perifoveal sectors, the extent of AL that may include 95% of the individuals became even narrower, from approximately 22.8 mm to 26.0 mm. The narrowest extent was observed in the perifoveal nasal sector, ranging from 23.3 mm to 25.5 mm. The effect of ocular magnification was more significant in hyperopes than in myopes in the inferior parafoveal sector and temporal, superior, and nasal perifoveal sectors. Conclusion: During macular ChT measurements, ocular magnification correction is not necessary in the central fovea. However, ocular magnification should be corrected normally in the nasal perifoveal region and in individuals with ALs shorter than 22.8 mm or longer than 26.0 mm in the remaining macular regions.